MiRNA-1183-targeted regulation of Bcl-2 contributes to the pathogenesis of rheumatic heart disease. Issue 11 (2nd November 2020) - Li, Ni; Zhu, Linwen; Zhou, Hua; Zheng, Dawei; Xu, Guodong; Sun, Lebo; Gao, Jianqing; Shao, Guofeng
Abstract: To determine whether up-regulation of miR-1183 targeting the gene for anti-apoptotic factor, B-cell lymphoma 2 (BCL-2) contributes to apoptosis in patients with rheumatic heart disease (RHD). Peripheral blood samples were isolated for miR-1183 characterization. The function of miRNA-1183 in RHD using miRNA mimic on PBMCs and THP-1 cell models. The binding of miR-1183 and Bcl-2 gene was confirmed by luciferase activity test. We also measured expression levels of BCL-2 in heart valve tissue from patients with RHD using ELISA and immunohistochemistry. In silico analysis and reporter gene assays indicated that miR-1183 directly targets the mRNA encoding BCL-2. It is found that miR-1183 binds directly to the 3′UTR of the BCL-2 mRNA and down-regulates the mRNA and protein levels of BCL-2. Overexpression of miR-1183 in RHD patients and cell lines down-regulated BCL-2 expression and induced apoptosis. With the progression of the disease, the expression of BCL-2 in the heart valve tissue of patients with RHD decreased. MiRNA-1183 is up-regulated in RHD and induces cardiac myocyte apoptosis through direct targeting and suppression of BCL-2, both of which might play important roles in RHD pathogenesis. During the compensatory period of RHD, up-regulated miR-1183 destroyed the balance of apoptosis proteins (Bax and BAK) in Bcl-2 family, enhance the apoptosis cascade reaction and reduce the anti apoptosis effect. The significantly higher expression levels of miR-1183 appear to play distinct roles in RHD pathogenesis by regulation BCL-2, possibly affecting myocardial apoptosis and remodeling in the context of RHD.